O desenho da família como técnica de investigação psicológica: influências da idade, sexo, e ordem de nascimento - Ortega, Antonio Carlos (1985)
This study is an investigation of the Family Drawing as a technique of psychological assessment with the purpose to assess its sensibility under the influence of age, sex and birth order. The sample was composed of 300 children, ages 7 to 9, males and females, belonging to families with two children and from the same socio-economic level. The Family Drawing technique was administered individually, with the instruction suggested by Porot CJ952): 'Draw your Family'. The drawings were analysed with the aid of a method developed for this study and based on the proposal of several authors. The method contained 52 characteristics in three levels: (a) general characteristics of the drawing, (b) level of the formal structures and Cc) content level. The results, analysed by means of the chi-square test ,revealed the sensibility of the technique. The majority of its characteristics were significantly associated ·with the variables. It was also shown that while the age influence was stronger in relationship to the general characteristics of the drawing and to the level of formal structures (which were predominantly explained in developmental and cognitive terms), the influences of sex and birth order were related to the characteristics of the level of formal structures and to content level (which were predominantly interpreted in projective and affective terms): It was further seen that the analysis of the characteristics significantly related to sex of the subject, allowed the statement and acceptance of a hypothesis about the sexual identification of the subjects with the parental figures (father and mother). Furthermore, analysis of the characteristics influenced by birth order allowed the formulation and acceptance of a hypothesis about sibling rivalry on the part of both the first born and the youngest. In conclusion, the fact that the majority of the authors consider the Family Drawing just a projective technique was questionned. Care in its interpretation was recommended. Finally, the investigation of some aspects related to birth order was suggested.